Diving into discomfort: orofacial pain dynamic—A systematic review - Lubna A. Alolaiwi; Fawziah A. Alzahrani; Sulaiman A. AlShammari (Frontiers in Public Health)
IntroductionScuba diving is a popular recreational activity. However, it carries inherent risks, including exposure to hyperbaric environments, which can exacerbate medical conditions, such as dental barotrauma, barodontalgia, temporomandibular disorders, and periodontal issues. Understanding the prevalence of orofacial pain among divers is critical for improving diver safety and health. Thus, this study aimed to investigate the occurrence and contributing factors of orofacial pain in various diver populations to inform targeted preventive strategies.MethodsA systematic literature search was conducted across PubMed, Saudi Digital Library, and Google Scholar, and articles that studied orofacial pain among divers were selected. The Joanna Briggs Institute was used to assess the risk of bias. Due to insufficient statistical data (e.g., confidence intervals, standard errors) and extremely high heterogeneity (I2 values of 97.23% for barodontalgia and 98.03% for dental barotrauma), a meta-analysis was deemed inappropriate, a synthesis without meta-analysis was conducted to assess the prevalence of various types of orofacial pain across diverse diver populations.ResultsThis review included seven studies that examined orofacial pain prevalence and some risk factors (e.g., diving depth, frequency, occupational duration, and oral health condition) among military, occupational, and recreational divers. Barodontalgia had the highest prevalence rate among the four types of orofacial pain studied in this review, ranging from 10.8% to 56.1%, whereas periodontal issues showed the lowest rate, ranging from 2.8 to 6.6%, and were the least frequently studied type of pain. Military divers were most affected by all types of pain.ConclusionThis study underscores the necessity of tailored preventive strategies for divers, particularly military and leisure divers. These strategies should focus on dental care, ergonomic interventions, oral hygiene education, equipment fitting, and clenching management.